ANALISIS PELAKSANAAN DESENTRALISASI DALAM OTONOMI DAERAH KOTA/KABUPATEN - Muhammad Mujtaba Habibi (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstrac : In order to implement regional autonomy based on Law No. 22 of 1999, that the granting of autonomy to the local city / county is based on the principle of decentralization in the form of autonomy, real, and responsible. Granting authority on the basis of the principle of decentralization, causing all fields are left to local governments in the implementation of an autonomous basically become the authority and responsibility of local city and county governments fully, both concerning the determination of policy, planning, implementation, monitoring, control, and evaluation. This study aimed to describe the factors that affect the implementation of regional autonomy and decen-tralization in the provision of recommendations for the implementation of decentralization in au-tonomy. The results showed that there are four variables that can explain the performance of the implementation of decentralization in the regional autonomy in the city / county, namely managerial aspects, aspects of Human Resources organization, aspects of bureaucratic culture, and ethics of public service.Keyword: decentralization, regional autonomy